Virtual Regional Fisheries Management Meetings in the Western and Central Pacific Ocean Region: A Preliminary Appraisal of Performance and Fit - Campbell, Brooke; McIlgorm, Alistair; Voyer, Michelle (Frontiers in Marine Science, 2021)
Regional fisheries meetings that support the management of Western and Central Pacific Ocean (WCPO) capture fisheries are usually held face-to-face and in-person. In 2020, the travel and gathering bans due to the global COVID-19 pandemic meant that these meetings were held ‘virtually’, primarily via videoconferencing. But can virtual meetings perform the same functions and deliver the same management outcomes as face-to-face meetings? This study is an initial investigation of the experiences, perceptions and attitudes of WCPO region government participants in a number of virtual regional fisheries meetings in 2020. Results indicate a strong preference for face-to-face regional meetings, with the perception that virtual meetings performed comparatively poorly at supporting a number of key meeting processes and outcomes. However, one-quarter to one-third of study participants consistently found no difference between format performance for many meeting processes and outcomes. Virtual formats were considered more appropriate for smaller and non-regional meetings, and allowed for greater staff attendance at meetings as well as cost and time savings for some, but not all, participants. Study participants believe that virtual regional meetings will be more common in the region in the future, despite nearly half indicating that virtual meeting are not a good fit for the region generally. Many of these experiences and perceptions are consistent with organisational behavior, communications media, and information systems literature. Some results appear unique to the region’s socially and culturally diverse Pacific island countries and territories, which are relative newcomers to the global information and communication technology ‘revolution’. A greater use of virtual regional fisheries meetings in the future requires meeting hosts and facilitators to carefully consider the potential impacts of virtual meetings on effective communication and inclusive participation in WCPO regional fisheries management and other governance outcomes.